THE INTELLECTUAL AND AESTHETIC DIMENSIONS OF EPIDEMIC SCENES IN CONTEMPORARY IRAQI PAINTING - Mohammed Ali Hasan Kadhim, Zahraa Hadi Kadhum (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The current research is concerned with presenting an intellectual reading of the works produced in modern Iraqi painting. Art has witnessed abundant intellectual and aesthetic theses in which opinions were sometimes in agreement and sometimes in opposition until it is no longer possible, especially in our contemporary world, to agree on a unified intellectual vision. The contemporary artist has transcended the data of the emergency perception that is reflected in art through realistic forms, and comes to complete his cognitive potentials of imagination and intuition where you find this energy. The search for representations of epidemics is to identify important topics related to the movement of society, as the work of art can have an aesthetic expressive value that influences it, and this reading is summarized as being cognitive, pouring within the framework of European painting, through its historical references on which it was based, and formed a mark In his career, and an important pillar of the civilized human culture and his emotional interactions, and considering the expressed artist as a being who works to change his civilized and natural reality, in line with his growing needs.